Diversity of brittle star and sea urchin (Echinoderm: Ophiuroidea, Echinoidea) of Krakal and Watu Kodok beach, Gunung Kidul, Yogyakarta. Issue 1 (July 2020) - Tarigan, R S; Hartati, R; Widowati, I
Abstract: Ophiuroidea and echinoidea are usually lived associated with coral reef and seaweed. Krakal and Watu Kodok Beach of Gunung Kidul Regency have characteristics of karst rocks, rubble and fast-current sea. They have large intertidal zone that allows ophiuroid and echinoid trapped among the basin during low tide. The research was aimed to identify and determine the diversity of Brittle Star and Sea Urchin in Krakal and Watu Kodok Beach. Survey was conducted on November-December 2018 at Krakal and Watu Kodok Beach. The samples were taken using quadrant transect method during low tide. The result of present work showed a total of 391 individuals belonging to Ophiocomidae Ophiuroid (2 species) and 279 individuals of 4 species echinoids belong to 2 families (Echinometridae and Diadematidae) lived in both beach. The highest abundance of Ophiocoma scolopendrina was found in Krakal beach (33.4 ind.m −2 ) while Echinometra oblonga was biggest in Watu Kodok beach (14.4 ind.m −2 ). In both location the diversity was low with medium to high similarity.